2020
DOI: 10.1097/htr.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Response to Adapted Cognitive Behavioral Therapy for Anxiety and Depression Following Traumatic Brain Injury

Abstract: Background: Given the high frequency and significance of anxiety and depression following traumatic brain injury (TBI), there is a need to evaluate the efficacy of psychological interventions and to understand factors influencing response to such interventions. The present study investigated factors associated with positive response to cognitive behavioral therapy adapted for cognitive impairments (CBT-ABI) for individuals with anxiety and depression following TBI, including demographic and injury-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
1
17
0
2
Order By: Relevance
“… Notes a Two research articles [ 67 , 100 ] reported two studies of different study designs and as such, data reported on study design are for 61 studies b All case studies c Excludes case studies; two before-after without control group, three controlled interventions d All conducted in the United States e Sixteen studies [ 49 51 , 53 , 62 , 67 , 68 , 74 , 76 , 83 , 89 , 90 , 92 , 99 , 103 , 104 ] examined integrated care for individuals with TBI and more than one type of MHSU f Some studies include more than one type of treatment and as such, the number of articles reported across treatment types exceeds 49 studies ED: Emergency department; MHSU: Mental health disorders or substance use; OT: Occupational therapy; PTSD: Post-traumatic stress disorder; rTMS: Repetitive transcranial magnetic stimulation; TBI: Traumatic brain injury …”
Section: Resultsmentioning
confidence: 99%
“… Notes a Two research articles [ 67 , 100 ] reported two studies of different study designs and as such, data reported on study design are for 61 studies b All case studies c Excludes case studies; two before-after without control group, three controlled interventions d All conducted in the United States e Sixteen studies [ 49 51 , 53 , 62 , 67 , 68 , 74 , 76 , 83 , 89 , 90 , 92 , 99 , 103 , 104 ] examined integrated care for individuals with TBI and more than one type of MHSU f Some studies include more than one type of treatment and as such, the number of articles reported across treatment types exceeds 49 studies ED: Emergency department; MHSU: Mental health disorders or substance use; OT: Occupational therapy; PTSD: Post-traumatic stress disorder; rTMS: Repetitive transcranial magnetic stimulation; TBI: Traumatic brain injury …”
Section: Resultsmentioning
confidence: 99%
“…Although treatment for these mood disorders will not be a focus of speech-language therapy, the impact of these disorders on cognitive communication must be understood and addressed (cf. Ponsford et al, 2020).…”
Section: Potential For Comorbid Psychiatric Conditionsmentioning
confidence: 99%
“…W ostatnich latach zwraca się również uwagę na zastosowanie oddziaływań poznawczo-behawioralnych w terapii pacjentów leczonych metodami zabiegowymi, m.in. z powodu urazów czaszkowo-mózgowych, urazów kręgosłupa, chorób zwyrodnieniowych lub procesów rozrostowych w obrębie ośrodkowego układu nerwowego (OUN) (Anson i Ponsford, 2006;Burke et al, 2019;Ponsford et al, 2020;Szepietowska-Ilach, 2018;Zelencich et al, 2020). Ukazują się prace dotyczące związku CBT z szybkością powrotu do pełnej aktywności zawodowej, z radzeniem sobie z bólem i leczeniem przeciwbólowym (Mariano et al, 2018;Rolving et al, 2015Rolving et al, , 2016Rolving et al, , 2014 u pacjentów przechodzących operacje kręgosłupa.…”
Section: Wstępunclassified
“…Natomiast w metaanalizie przeprowadzonej przez innych badaczy stwierdzono skuteczność CBT w leczeniu depresji -siła efektu mieściła się w przedziale 0-3,47 z przeciętną 1,15 (Waldron et al, 2013). Terapia poznawczo-behawioralna nie tylko okazała się efektywna w redukcji lęku i depresji u pacjentów po łagodnym lub ciężkim urazie, ale także przyczyniała się do ich lepszego funkcjonowania psychospołecznego (Ponsford et al, 2016(Ponsford et al, , 2020. Stwierdzono też korzystny wpływ technik CBT na kontrolę złości (Hart et al, 2017;Walker et al, 2010) i redukcję agresywności (Aboulafia-Brakha et al, 2013) w analizowanej grupie chorych.…”
Section: Guzy Mózguunclassified